Hadith #2834 - Sunan Abi Dawud - Abu Yazid al-Makki أبو يزيد المكي; Masdad bin Masrhad مسدد بن مسرهد بن مسربل; Saba' bin Thabit; Sufyan bin Sa‘id Ath-Thawri سفيان الثوري; Ubaidullah bin Abi Yazid عبيد الله بن أبي يزيد المكي (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say: Two resembling sheep are to be sacrificed for a boy and one for a girl. AbuDawud said: I heard Ahmad (ibn Hanbal) say: The Arabic word mukafi’atani means equal (in age) or resembling each other.
Grade: Sahih